2021
DOI: 10.3390/su13041984
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ecological Knowledge on Young Consumers’ Attitudes and Behaviours towards the Food Market

Abstract: The subject literature around the world puts a strong emphasis on the discrepancy between the positive attitude towards the idea of sustainability and consumer behaviour. These issues are the subject matter of this paper, which aims at both the identification and evaluation of selected aspects of knowledge, attitudes and eco-friendly behaviour of consumers connected with their choice of foods. The authors made an attempt of answering the question, to what extent do the level of knowledge and the declared eco-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 81 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…Consumers with a high level of ecological awareness are more often involved in purchasing ecological products [74]. Raising awareness therefore helps to stimulate the demand for organic products [75]. Consumers who are more knowledgeable about the environment show a higher tendency to act positively on environmental issues [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Consumers with a high level of ecological awareness are more often involved in purchasing ecological products [74]. Raising awareness therefore helps to stimulate the demand for organic products [75]. Consumers who are more knowledgeable about the environment show a higher tendency to act positively on environmental issues [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the literature, it emerges that younger respondents often have a lower spending budget, so they could be less prone to spend on food [65]. Although, other research found that younger consumers are the most sensitive to environmental issues and sustainability [80,81], which will require further clarification in future research.…”
Section: Discussionmentioning
confidence: 95%
“…Kaliyaperumal (2004) defined knowledge as "understanding of any subject," attitude as "feelings toward that subject along with predetermined opinions," and practice as "ways of demonstrating their knowledge and attitudes through their actions." The KAP model has been used in various environmental studies (Ahmad et al, 2015, Ahamad & Ariffin, 2018Kumar et al, 2019;Kuźniar et al, 2021;Öztürk, 2022). In this study, based on the KAP model, the knowledge (environmental value), attitude (green consumption attitude), and practices (green buying behavior) of Turkish university students were assessed in relation to environmental consumption.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In addition, it has been widely thought in the literature that reasons such as green product knowledge, awareness and environmental concerns of the consumer have an impact on consumers' green product purchasing behavior (Dhir et al, 2021;Sharma, 2021;Wang et al, 2021). Meanwhile, it has been observed that consumers' awareness and environmental behavior towards environmentally friendly products has increased (Kuźniar et al, 2021). However, demand for eco-friendly products did not increase as much as anticipated (Lai & Cheng, 2016).…”
Section: Introductionmentioning
confidence: 98%